Validity of retrospective session rating of perceived exertion to quantify training load in youth athletes - Scantlebury, S.; Till, K.; Sawczuk, T.; Phibbs, P.; Jones, B. (The Journal of Strength and Conditioning Research, 2018)
Youth athletes frequently participate in multiple sports or for multiple teams within the same sport. To optimize player development and minimize undesirable training outcomes (e.g., overuse injuries), practitioners must be cognizant of an athlete's training load within and outside their practice. This study aimed to establish the validity of a 24-hour (s-RPE24) and 72-hour (s-RPE72) recall of session rating of perceived exertion (s-RPE) against the criterion measure of s-RPE collected 30 minutes' post training (s-RPE30). Thirty-eight adolescent athletes provided a s-RPE30 following the first field based training session of the week. Approximately 24 hours later subjects were asked to recall the intensity and duration of the previous days training. The following week subjects once again provided an s-RPE30 measure after training before recalling the intensity and duration of the session approximately 72 hours later. A nearly perfect correlation (0.98 [0.97-0.99]) was found between s-RPE30 and s-RPE24, with a small typical error of estimate (TEE; 8.3% [6.9-10.5]) and trivial mean bias (-1.1% [-2.8 to 0.6]). Despite a large correlation between s-RPE30 and s-RPE72 (0.73 [0.59-0.82]) and a trivial mean bias (-0.2% [-6.8 to 6.8]), there was a large TEE (35.3% [29.6-43.9]). s-RPE24 provides a valid measure of retrospectively quantifying s-RPE; however, the large error associated with s-RPE72 suggests that it is not a suitable method for monitoring training load in youth athletes.